PENGARUH PENERAPAN STRATEGI PEMBELAJARAN JOYFUL LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR KELAS III SD INPRES 130 TAROWANG KABUPATEN JENEPONTO - Hatmawati Hatmawati; Safei Safei; Andi Dian Angriani; Rosdiana Rosdiana (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine whether there is an effect of implementing joyful learninglearning strategies on student learning outcomes in third grade mathematics at SDInpres 130 Tarowang, Jeneponto Regency. The type of research used in this study is thetype of research One Group pretest-posttest. Data collection in this study using tests andobservations. Data were analyzed using descriptive statistical techniques and inferentialstatistics. The results of the analysis show that the application of the joyful learningstrategy has an effect on mathematics learning outcomes for third grade students of SDInpres 130 Tarowang, Jeneponto Regency. In addition, learning mathematics with ajoyful learning strategy can improve the quality of mathematics learning, namelyincreasing the comfort of students during learning, increasing student activity andincreasing interest in participating in mathematics learning.